PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, FIRM SIZE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTIES AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Winda Rizky Amalia; Purwohandoko Purwohandoko; Ulil Hartono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to analyze the effect of profitability, liquidity, leverage, firm size, and dividend policy on company value in properties and real estate sector companies listed on the Indonesian stock exchange for the 2019-2021 period. The type of data used is quantitative data sourced from secondary data. This research's populations are companies in the properties and real estate sector listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, and obtained 15 companies as samples. The data analysis technique used is multiple linear regression. The results show that profitability does not affect firm value, liquidity does not affect firm value, leverage does not affect firm value, firm size has a positive and significant impact on firm value, and dividend policy does not affect firm value. Therefore, this study recommends that companies increase firm size based on total assets owned so that firm value can also increase. Investors can consider the company's firm size when making investment decisions.